Risk Factors Associated with Low Anterior Resection Syndrome: A Cross-Sectional Study - Liang, Lim See (2020)
Introduction: Oncological outcomes following rectal cancer surgery have improved significantly over recent decades with lower recurrences and longer overall survival. However, these survival advantages have greatly overshadowed functional outcomes of surgery, which are poor for many patients and consistently under-reported. Many of the patients experienced several bowel symptoms after surgery, which include flatus and faeces incontinence, frequent bowel opening, urgency or sense of incomplete defecation. This combination of such symptoms after sphincter preserving surgery is referred as Low Anterior Resection Syndrome (LARS). Aim: The aim of this study is to identify the prevalence and risk factors associated with development of LARS. Methods: This is a cross-sectional study from 2 tertiary hospitals with colorectal unit in Kelantan. All patients who were diagnosed with rectal cancer and had undergone sphincter-preserving low anterior resection at the participating hospitals between January 2011 and December 2020 were eligible. Upon clinic follow up, patients were asked to complete an interviewed based simple questionnaire (LARS score) designed to assess bowel dysfunction after rectal cancer surgery. Patients were grouped into two separate cohorts—those with major LARS scores and those with mild/no LARS symptoms. Categorical outcomes were compared for the major LARS group. Results: A total of 76 patients who fulfilled subject criteria recruited from clinic from those who had sphincter preserving rectal surgery for rectal cancer in participating hospital. There were 25 (32.8%) patients with major LARS, 10 (13.1%) patients minor LARS, and 41 (53.9%) patients with no LARS. Height of tumour from anal verge showed the association (P value =0.039) with development of major LARS. Those patients with less than 8cm tumour from anal verge increased risk of LARS by three times compared to those with 8cm and above (Adjusted OR (95% CI) = 3.11 (1.06,9.13)). Conclusion: We identified low tumour height as a significant risk factor which has negative impact on bowel function after surgery. The high prevalence of LARS emphasizes the need of study regarding risk factor and importance of understanding pathophysiology of LARS, in order for us to improve patient bowel function and quality of life after rectal cancer surgery